Legislative Update Q3 - ibrachy & dermarkar law firm (ibrachy & dermarkar law firm, 2025)
Official Journal – Issue 23 (Bis - A) Dated 10 June, 2025. Law No. 87 of the Year 2025 Amending Certain Provisions of Law No. 198 of the Year 2014 Promulgating the Law on Mineral Resources and the accompanying law.